A nano-modified all-solid waste mine filling material and its preparation method and application
By using a variety of industrial solid waste and weak alkali exciters to prepare nanomodified all-solid waste mine filling materials, the problems of high cost and low efficiency of traditional filling materials are solved, and efficient resource utilization and material performance are achieved.
Patent Information
- Application Number
- CN202410717041.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-06-04
AI Technical Summary
The existing mine filling materials have problems such as high cost, low efficiency, insufficient strength and slow condensation. The traditional alkaline excitants are limited in use and cannot effectively utilize a variety of industrial solid waste.
Industrial solid waste such as nickel slag, fly ash microbeads, calcium carbide slag, municipal waste incineration ash and gold ore tailings sand are used as raw materials, combined with sodium carbonate as a weak alkali exciter, and nano-modified all-solid waste mine filling materials are prepared through the modification of nanosilicon dioxide and nanotitanium dioxide.
It realizes efficient resource utilization, environmental protection and energy saving, and low-cost production. The materials have rapid solidification, high compressive strength and good durability, and are suitable for a variety of engineering needs.
Smart Images

Figure BDA0004875873200000101 
Figure BDA0004875873200000111 
Figure BDA0004875873200000112
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of industrial solid waste resource utilization, and in particular to a nano-modified all-solid waste mine filling material and a preparation method and application thereof. Background Art
[0002] Alkali-activated cementitious materials technology is an important research direction in the field of green and environmentally friendly building materials. This type of material uses industrial solid wastes such as slag, fly ash, and kaolin as the main raw materials, activates potential hydraulic activity under alkaline conditions, and becomes an environmentally friendly alternative to traditional cementitious materials. Its advantages are abundant raw material resources, high strength, low cost, and significant environmental protection characteristics. It also has good corrosion resistance, fire resistance, and the ability to fix heavy metal ions. However, existing research focuses on the single selection of raw materials, which cannot give full play to the advantages of the coordinated treatment of various industrial solid wastes; on the other hand, alkaline activators mostly use strong alkali systems such as water glass and sodium hydroxide, while weak alkali activators such as sodium carbonate have the advantages of low carbon and low alkali, but face challenges such as long setting time and low early strength, which limits their wide application.
[0003] Faced with the underground cavities and ground collapse caused by energy mining, traditional mine filling materials have defects such as high cost, low efficiency, insufficient strength and slow solidification, and there is an urgent need for a more cost-effective and better performance filling material. In view of this, the use of multi-source solid waste synergistic effect to prepare backfill materials has become an ideal solution, which can effectively utilize industrial waste and meet economic and environmental requirements.
[0004] Therefore, there is an urgent need to develop a low-carbon, low-alkali mine filling material that can not only utilize a variety of solid wastes as resources, but also use a weak base activator. Summary of the invention
[0005] In order to solve the deficiencies of the prior art, the present invention provides a nano-modified all-solid waste mine filling material and its preparation method and application, aiming to provide a method using nickel slag, fly ash microbeads, municipal waste incineration ash and carbide slag as precursors, weak base sodium carbonate as an activator, and combined with nano materials such as nano silicon dioxide and nano titanium dioxide for modification to reduce the adverse effects of weak bases, using coal gangue as coarse aggregate and gold mine tailings as fine aggregate, to prepare a new nano material modified all-solid waste concrete that can be used as a mine backfill material. The method for preparing nano-modified all-solid waste mine filling material of the present invention can not only effectively utilize solid waste resources and reduce environmental pollution, but also overcome the defects of sodium carbonate-activated cementitious materials by adjusting the composition of the precursor and the modification of the nano material, and provide a mine backfill material with a simple process and adjustable setting time and strength according to requirements.
[0006] Specifically, the present invention provides a nano-modified all-solid waste mine filling material, which comprises the following components by weight:
[0007] 25-36.4 parts of blast furnace nickel slag; 25-35.3 parts of calcium carbide slag; 18.2-25 parts of fly ash microspheres; 15.7-25 parts of municipal waste incineration ash; 2-6 parts of sodium carbonate; 35-50 parts of water; 100-200 parts of gold mine tailings; 125-250 parts of coal gangue; 1.2-1.8 parts of sodium citrate; 1.0-1.4 parts of tartaric acid; 0.56-1.4 parts of nano-silicon dioxide; 0.84-1.4 parts of nano-titanium dioxide.
[0008] In some specific embodiments of the present invention, the sodium carbonate is 4 parts; the water is 35 parts.
[0009] In some specific embodiments of the present invention, the CaO content in the carbide slag is above 96%; the SiO2 content in the fly ash microspheres is 55%, the Al2O3 content is 23.5%, and the Fe2O3 content is 6.8%; the SiO2 content in the blast furnace nickel slag is 33.3%, the CaO content is 22.3%, and the Al2O3 content is 16%; the SiO2 content in the municipal waste incineration ash is 28%, and the CaO content is 54%.
[0010] In some specific embodiments of the present invention, the CaO content in the carbide slag is 97.5%; the SiO2 content in the fly ash microspheres is 59.4%, the Al2O3 content is 23.3%, and the Fe2O3 content is 5.5%; the SiO2 content in the blast furnace nickel slag is 33.15%, the CaO content is 22.5%, and the Al2O3 content is 21.94%; the SiO2 content in the municipal waste incineration ash is 31.2%, and the CaO content is 53.9%.
[0011] The present invention also provides a method for preparing the above-mentioned nano-modified all-solid waste mine filling material, comprising the following steps:
[0012] S1. Raw material drying: drying blast furnace nickel slag, carbide slag, fly ash microbeads and municipal waste incineration ash;
[0013] S2. Raw material grinding: The dried blast furnace nickel slag, carbide slag, municipal waste incineration ash were ground separately, and then sieved, the sieved powdered blast furnace nickel slag, carbide slag, fly ash beads, municipal waste incineration ash and dried fly ash beads were mixed in parts by weight to obtain a composite powder;
[0014] S3. Raw material ratio: Weigh the solid sodium carbonate particles in parts by weight;
[0015] S4. Mixing and stirring: Add nano silicon dioxide and nano titanium dioxide to part of the water and dissolve them completely by physical methods; then pour the composite powder in S2 and the solid sodium carbonate particles in S3 into a mixer and dry mix at a low speed; then pour the remaining water, tartaric acid, sodium citrate and the suspension of nano silicon dioxide and nano titanium dioxide into the mixer, mix them thoroughly to obtain the prepared nano-modified alkali-activated multi-component composite cementitious material; finally, add coal gangue and gold tailings as coarse and fine aggregates, stir thoroughly to obtain nano-modified alkali-activated concrete, that is, nano-modified all-solid waste mine filling material.
[0016] In some specific embodiments of the present invention, the drying time in S1 is 14 hours, and the drying temperature is controlled at 50°C.
[0017] In some specific embodiments of the present invention, the drying time in S1 is 20 hours.
[0018] In some specific embodiments of the present invention, the grinding time in S2 is 50 min, and the sieving in S2 is through a 200-mesh sieve.
[0019] In some specific embodiments of the present invention, the grinding time in S2 is 60 min.
[0020] In some specific embodiments of the present invention, the grinding time in S2 is 70 min, and the sieving in S2 is through a 200-mesh sieve.
[0021] In some specific embodiments of the present invention, the dry mixing time in S4 is 50s; after the remaining water, tartaric acid, sodium citrate and nano-silicon dioxide and nano-titanium dioxide suspension are poured into the mixer in S4 and rotated and stirred for 50s, aggregate is added to S4 and rotated and stirred for 120s.
[0022] In some specific embodiments of the present invention, the dry mixing time in S4 is 30 seconds; after the remaining water, tartaric acid, sodium citrate and nano-silicon dioxide and nano-titanium dioxide suspension are poured into the mixer in S4 and rotated and stirred for 60 seconds, the aggregate is added to S4 and rotated and stirred for 120 seconds.
[0023] In some specific embodiments of the present invention, the physical method in S4 includes mechanical stirring.
[0024] In some specific embodiments of the present invention, the physical method in S4 includes mechanical stirring and ultrasonic dispersion.
[0025] The present invention also provides a building material, comprising the nano-modified all-solid waste mine filling material or the nano-modified all-solid waste mine filling material prepared by the method for preparing the nano-modified all-solid waste mine filling material.
[0026] The present invention also provides the use of the nano-modified all-solid waste mine filling material or the nano-modified all-solid waste mine filling material prepared by the preparation method of the nano-modified all-solid waste mine filling material in mine backfilling projects, construction projects, bridge projects, highway projects or tunnel projects.
[0027] Compared with the prior art, the present invention has the following significant advantages and effects:
[0028] 1. Efficient resource utilization and waste treatment: By using a large amount of industrial waste residues such as nickel slag, fly ash microbeads, carbide slag, gold mine tailings, coal gangue as raw materials, it not only effectively reduces production costs, but also finds new treatment methods for these large solid wastes, reduces the occupation of land resources and environmental pollution, and embodies the concept of circular economy and sustainable development.
[0029] 2. Environmental protection, energy saving and low cost: It has the characteristics of "all solid waste" and "no sintering". It can be used after mixing at room temperature, which greatly saves energy consumption and reduces carbon emissions, simplifies the production process, reduces the cost of filling materials, and only requires a small amount of nanomaterials as additives to achieve excellent filling performance.
[0030] 3. Safe and convenient application of activator: Compared with the traditional water glass activator, the use of sodium carbonate as an activator is easier to operate and less dangerous. Sodium carbonate does not need to adjust the modulus and can be directly mixed with the cementitious material. Its low pH value reduces the operating risk. At the same time, the low shrinkage rate of the sodium carbonate activator system improves the volume stability and reduces the risk of structural cracking.
[0031] 4. High performance and rapid solidification: Through the carefully designed component ratio, especially the synergistic effect of weak alkaline sodium carbonate and other waste residues and nanomaterials, rapid solidification (initial setting in 12 minutes, final setting in 23 minutes) and high compressive strength (≥5.0MPa in 2 hours to ≥40MPa in 28 days) are achieved, indicating that this material is a high-performance, fast-setting filling material suitable for a variety of engineering needs.
[0032] 5. Enhanced material performance and durability: The introduction of nanomaterials such as silica and titanium dioxide not only improves the early strength and hydration degree, but also enhances the density and durability of the material by modifying the microstructure, thereby improving the overall mechanical properties.
[0033] 6. Environmental and economic benefits: Taking into account the above technical effects, this invention is not only conducive to the widespread application of alkali-activated materials and lays the foundation for the research and development of new energy-saving building materials, but also brings significant economic, social and environmental benefits, including reducing land damage, alleviating environmental pollution, and promoting the green transformation of the building materials industry.
[0034] In summary, the present invention has successfully developed a new type of weak alkali-activated concrete that is both environmentally friendly and efficient by innovatively utilizing industrial waste slag and combining it with nanotechnology. Its technical solution has demonstrated important technological progress and social value at multiple levels. DETAILED DESCRIPTION
[0035] In conjunction with specific embodiments, the present invention will be further described. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the application.
[0036] Example 1: Preparation of non-nano-modified all-solid waste mine filling material and nano-modified all-solid waste mine filling material
[0037] Comparative Scheme 1: Put blast furnace nickel slag, carbide slag, fly ash microbeads and municipal waste incineration ash into a dryer for 24 hours, and the drying temperature is controlled at 60°C; put the dried blast furnace nickel slag, carbide slag and municipal waste incineration ash into a closed grinder for 70 minutes, then take them out and pass them through a 200-mesh sieve, and sieve the powdered blast furnace nickel slag, carbide slag, municipal waste incineration ash and dried fly ash microbeads according to the ratio of 25 parts of nickel slag, 25 parts of fly ash microbeads, 25 parts of carbide slag and 25 parts of municipal waste incineration ash. The weight proportion is used to mix the powders to obtain a composite powder; 4 parts of solid sodium carbonate particles are weighed; then the composite powder and the weighed solid sodium carbonate particles are poured into a mixer and dry-mixed at a low speed for 30 seconds; then 35 parts of water, 1 part of tartaric acid, and 1.2 parts of sodium citrate are poured into the mixer, and the mixture is rotated and stirred for 60 seconds, and the prepared alkali-activated multi-component composite cementitious material is obtained after sufficient mixing; finally, 250 parts of coal gangue and 200 parts of gold tailings are added, and the mixer is rotated and stirred for 120 seconds, and the alkali-activated concrete is obtained after sufficient mixing. The obtained alkali-activated concrete is placed in a curing room at a temperature of 20°C and a humidity of 95% and cured until the test date (2h, 1d, 3d, 7d, 28d).
[0038] Comparative Scheme 2: Put blast furnace nickel slag, carbide slag, fly ash microbeads and municipal waste incineration ash into a dryer for 24 hours, and the drying temperature is controlled at 60°C; put the dried blast furnace nickel slag, carbide slag and municipal waste incineration ash into a closed grinder for 70 minutes, then take them out and pass them through a 200-mesh sieve, and sieve the powdered blast furnace nickel slag, carbide slag, municipal waste incineration ash and dried fly ash microbeads according to the ratio of 36.4 parts of nickel slag, 18.2 parts of fly ash microbeads, 27.3 parts of carbide slag and 18.6 parts of municipal waste incineration ash. .1 parts by weight ratio for powder mixing to obtain composite powder; weigh 4 parts of solid sodium carbonate particles; then pour the above composite powder and the weighed solid sodium carbonate particles into a mixer and dry mix at low speed for 30 seconds; then pour 35 parts of water, 1 part of tartaric acid, and 1.2 parts of sodium citrate into the mixer, continue to rotate and stir for 60 seconds, and obtain the prepared alkali-activated multi-component composite cementitious material after sufficient mixing; finally add 250 parts of coal gangue and 200 parts of gold tailings sand, and then continue to rotate and stir the mixer for 120 seconds, and fully stir to obtain alkali-activated concrete. The obtained alkali-activated concrete is placed in a curing room with a temperature of 20°C and a humidity of 95% and cured until the test date (2h, 1d, 3d, 7d, 28d).
[0039] Comparative Scheme 3: Put blast furnace nickel slag, carbide slag, fly ash microbeads and municipal waste incineration ash into a dryer for 24 hours, and the drying temperature is controlled at 60°C; put the dried blast furnace nickel slag, carbide slag and municipal waste incineration ash into a closed grinder for 70 minutes, then take them out and pass them through a 200-mesh sieve, and sieve the powdered blast furnace nickel slag, carbide slag, municipal waste incineration ash and dried fly ash microbeads according to the ratio of 27.5 parts of nickel slag, 21.6 parts of fly ash microbeads, 35.3 parts of carbide slag, and 15.6 parts of municipal waste incineration ash. .7 parts by weight ratio for powder mixing to obtain composite powder; weigh 4 parts of solid sodium carbonate particles; then pour the above composite powder and the weighed solid sodium carbonate particles into a mixer and dry mix at low speed for 30 seconds; then pour 35 parts of water, 1 part of tartaric acid, and 1.2 parts of sodium citrate into the mixer, continue to rotate and stir for 60 seconds, and obtain the prepared alkali-activated multi-component composite cementitious material after sufficient mixing; finally add 250 parts of coal gangue and 200 parts of gold tailings sand, and then continue to rotate and stir the mixer for 120 seconds, and fully stir to obtain alkali-activated concrete. The obtained alkali-activated concrete is placed in a curing room with a temperature of 20°C and a humidity of 95% and cured until the test date (2h, 1d, 3d, 7d, 28d).
[0040] Implementation scheme 1: put blast furnace nickel slag, carbide slag, fly ash microbeads and municipal waste incineration ash into a dryer for drying for 24 hours, and the drying temperature is controlled at 60°C; put the dried blast furnace nickel slag, carbide slag and municipal waste incineration ash into a closed grinder for grinding for 70 minutes, then take them out and pass them through a 200-mesh sieve, and mix the sieved powdered blast furnace nickel slag, carbide slag, municipal waste incineration ash and dried fly ash microbeads according to the weight ratio of 25 parts of nickel slag, 25 parts of fly ash microbeads, 25 parts of carbide slag and 25 parts of municipal waste incineration ash to obtain a composite powder; weigh 4 parts of solid sodium carbonate particles; add 1.4 parts of nano silicon dioxide into water ( Use part of the water in 35 parts of water) to completely dissolve it by physical methods; then pour the above composite powder and the weighed solid sodium carbonate particles into a mixer and dry mix at low speed for 30 seconds; then pour the remaining water, 1 part of tartaric acid, 1.2 parts of sodium citrate and the above dissolved nano-silicon dioxide suspension into the mixer, continue to rotate and stir for 60 seconds, and after fully mixing, obtain the prepared nano-modified alkali-activated multi-component composite cementitious material; finally, add 250 parts of coal gangue and 200 parts of gold tailings as coarse and fine aggregates, and then continue to rotate and stir the mixer for 120 seconds, and fully stir to obtain nano-modified alkali-activated concrete, that is, nano-modified all-solid waste mine filling material. The obtained nano-modified alkali-activated concrete is placed in a curing room with a temperature of 20°C and a humidity of 95% and cured until the test date (2h, 1d, 3d, 7d, 28d).
[0041] Implementation Plan 2: Put blast furnace nickel slag, carbide slag, fly ash microbeads and municipal waste incineration ash into a dryer for drying for 24 hours, and the drying temperature is controlled at 60°C; put the dried blast furnace nickel slag, carbide slag and municipal waste incineration ash into a closed grinder for grinding for 70 minutes, then take them out and pass them through a 200-mesh sieve, and mix the sieved powdered blast furnace nickel slag, carbide slag, municipal waste incineration ash and dried fly ash microbeads according to the weight ratio of 25 parts of nickel slag, 25 parts of fly ash microbeads, 25 parts of carbide slag and 25 parts of municipal waste incineration ash to obtain a composite powder; weigh 4 parts of solid sodium carbonate particles; add 1.4 parts of nano titanium dioxide into the mixture; Water (part of 35 parts of water is used) is completely dissolved by physical methods; then the composite powder and the weighed solid sodium carbonate particles are poured into a mixer and dry-mixed at low speed for 30 seconds; then the remaining water, 1.2 parts of tartaric acid, 1.8 parts of sodium citrate and the above-dissolved nano titanium dioxide suspension are poured into the mixer, and the mixture is rotated and stirred for 60 seconds. After fully mixing, the prepared nano-modified alkali-activated multi-component composite cementitious material is obtained; finally, 250 parts of coal gangue and 200 parts of gold tailings are added, and the mixer is rotated and stirred for 120 seconds, and the nano-modified alkali-activated concrete is obtained after fully mixing, i.e., the nano-modified all-solid waste mine filling material. The obtained nano-modified alkali-activated concrete is placed in a curing room at a temperature of 20°C and a humidity of 95% and cured until the test date (2h, 1d, 3d, 7d, 28d).
[0042] Implementation Plan 3: Put blast furnace nickel slag, carbide slag, fly ash microbeads and municipal waste incineration ash into a dryer for drying for 24 hours, and the drying temperature is controlled at 60°C; put the dried blast furnace nickel slag, carbide slag and municipal waste incineration ash into a closed grinder for grinding for 70 minutes, then take them out and pass them through a 200-mesh sieve, and mix the sieved powdered blast furnace nickel slag, carbide slag, municipal waste incineration ash and dried fly ash microbeads according to the weight ratio of 25 parts of nickel slag, 25 parts of fly ash microbeads, 25 parts of carbide slag and 25 parts of municipal waste incineration ash to obtain a composite powder; weigh 4 parts of solid sodium carbonate particles; add 0.56 parts of nano silicon dioxide and 0.84 parts of nano titanium dioxide. 1.5 parts of tartaric acid, 1.2 parts of sodium citrate, and the above-dissolved nano-silicon dioxide and nano-titanium dioxide suspensions are poured into the mixer, and the mixture is rotated and stirred for 60 seconds. After being fully mixed, the prepared nano-modified alkali-activated multi-component composite cementitious material is obtained. Finally, 250 parts of coal gangue and 200 parts of gold tailings are added, and the mixer is rotated and stirred for 120 seconds. The nano-modified alkali-activated concrete, i.e., the nano-modified all-solid waste mine filling material, is obtained by fully mixing. The obtained nano-modified alkali-activated concrete is placed in a curing room at a temperature of 20°C and a humidity of 95% and cured until the test date (2h, 1d, 3d, 7d, 28d).
[0043] Implementation scheme 4: Put blast furnace nickel slag, carbide slag, fly ash microbeads and municipal waste incineration ash into a dryer for drying for 24 hours, and the drying temperature is controlled at 60°C; put the dried blast furnace nickel slag, carbide slag and municipal waste incineration ash into a closed grinder for grinding for 70 minutes, then take them out and pass them through a 200-mesh sieve, and mix the sieved powdered blast furnace nickel slag, carbide slag, municipal waste incineration ash and dried fly ash microbeads according to the weight ratio of 27.5 parts of blast furnace nickel slag, 21.6 parts of fly ash microbeads, 35.3 parts of carbide slag and 15.7 parts of municipal waste incineration ash to obtain a composite powder; weigh 4 parts of solid sodium carbonate particles; add 0.56 parts of nano silicon dioxide and 0.56 parts of nano silicon dioxide. 0.84 parts of titanium are added to water (part of the water in 35 parts of water is used) and completely dissolved by physical methods; then the above composite powder and the weighed solid sodium carbonate particles are poured into a mixer and dry-mixed at low speed for 30 seconds; then the remaining parts of water, 1.4 parts of tartaric acid, 1.2 parts of sodium citrate and the above dissolved nano-silicon dioxide and nano-titanium dioxide suspension are poured into the mixer, and the mixture is rotated and stirred for 60 seconds. After fully mixing, the prepared nano-modified alkali-activated multi-component composite cementitious material is obtained; finally, 250 parts of coal gangue and 200 parts of gold tailings are added, and the mixer is rotated and stirred for 120 seconds, and the nano-modified alkali-activated concrete, i.e., nano-modified all-solid waste mine filling material, is obtained by fully mixing. The obtained nano-modified alkali-activated concrete is placed in a curing room at a temperature of 20°C and a humidity of 95% and cured until the test date (2h, 1d, 3d, 7d, 28d).
[0044] The sodium carbonate used in this embodiment is solid particles, and the purity specification is analytical grade.
[0045] The carbide slag used in this embodiment has a CaO content of 96%; the fly ash microspheres have a SiO2 content of 59.4%, an Al2O3 content of 23.3%, and a Fe2O3 content of 5.5%; the blast furnace nickel slag has a SiO2 content of 33.15%, a CaO content of 22.5%, and an Al2O3 content of 21.94%. The municipal waste incineration ash has a SiO2 content of 31.2% and a CaO content of 53.9%.
[0046] The results of the physical and mechanical properties of the gangue aggregate used in this embodiment are shown in Table 1. According to GB / T14685-2011 "Pebbles and Crushed Stones for Construction", the particle gradation of gangue meets the standard requirements of Class III, so gangue meets the requirements as coarse aggregate for concrete.
[0047] Table 1 Comparison of physical and mechanical properties of coal gangue aggregate
[0048] Physical properties Coal Gangue Natural gravel Particle gradation / mm 5~25 5~25 <![CDATA[Bulk density / kg·m 3 > 1187 1302 <![CDATA[Apparent density / kg·m 3 > 2429 2717 Water absorption / % 5.5 1.2 Crushing index / % 20.8 11.2
[0049] The physical and mechanical properties of the gold tailings fine aggregate used in this embodiment are shown in Table 2. According to GB / T 14685-2011 "Pebbles and Crushed Stones for Construction", the particle gradation of gold tailings meets the standard requirements of Class III, so gold tailings meet the requirements as fine aggregate for concrete.
[0050] Table 2 Comparison of physical and mechanical properties of gold mine tailings fine aggregate
[0051]
[0052]
[0053] Example 2: Testing of non-nano-modified all-solid waste mine filling materials and nano-modified all-solid waste mine filling materials
[0054] The test block preparation method refers to the "Test Method for Cement Mortar Strength (ISO Method)" (GB / T 17671-2021); the "Test Method for Cement Paste Fluidity" (GB / T 2419), and the "Test Method for Cement Standard Consistency Water Consumption, Setting Time, and Stability" (GB / T 1346-2011), and the non-nano-modified all-solid waste mine filling materials and nano-modified all-solid waste mine filling materials prepared by the above-mentioned comparative schemes and implementation schemes are designed and tested, and the final compressive strength, fluidity and setting time data are shown in Table 3 and Table 4 respectively. By comparison, it can be seen that after adding the nano-modified material, the nano-modified all-solid waste mine filling material provided by the present invention sets quickly, and the initial setting time and final setting time are greatly advanced, and the effect of nano-titanium dioxide is better than that of nano-silicon dioxide when acting alone, but the effect of the two is better than that of the two alone when they are mixed in a certain proportion. Using coal gangue and gold mine tailings as coarse and fine aggregates, the strength of the system is not reduced, but improved through the specific ratio of precursors and the effects of admixtures and modifying materials. The early compressive strength and late compressive strength of the control group are significantly higher than those before modification. The performance of the nano-modified all-solid waste mine filling material provided by the present invention is inseparable from the specific ratio of the precursors.
[0055] Table 3 Compressive strength data of solid waste mine filling materials prepared by various schemes in Example 1
[0056]
[0057] Table 4 Fluidity and setting time data of solid waste mine filling materials prepared by various schemes in Example 1
[0058] Comparison plan Initial setting time / min Final setting time / min Fluidity / mm 1 227 280 210 2 207 314 183 3 155 240 190 Implementation Initial setting time / min Final setting time / min Fluidity / mm 1 88 120 140 2 36 77 172 3 22 48 177 4 12 23 188
[0059] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A nano-modified all-solid waste mine filling material, characterized in that: By weight, it includes the following components: 25-36.4 parts of blast furnace nickel slag; 25-35.3 parts of calcium carbide slag; 18.2-25 parts of fly ash microspheres; 15.7-25 parts of municipal waste incineration ash; 2-6 parts of sodium carbonate; 35-50 parts of water; 100-200 parts of gold mine tailings; 125-250 parts of coal gangue; 1.2-1.8 parts of sodium citrate; 1.0-1.4 parts of tartaric acid; Nano silicon dioxide 0.56-1.4 parts; Nano titanium dioxide 0.84-1.4 parts; In terms of weight percentage, the CaO content in the carbide slag is more than 95%; the SiO2 content in the fly ash microspheres is 50%-65%, the Al2O3 content is 20%-30%, and the Fe2O3 content is 5%-8%; the SiO2 content in the blast furnace nickel slag is 30%-50%, the CaO content is 20%-30%, and the Al2O3 content is 15%-30%; the SiO2 content in the municipal waste incineration ash is 25%-40%, and the CaO content is 40%-60%.
2. The method for preparing the nano-modified all-solid waste mine filling material according to claim 1, characterized in that: The steps include: S1. Drying of raw materials: Drying blast furnace nickel slag, carbide slag, fly ash microbeads and municipal waste incineration ash according to weight proportions; S2. Raw material grinding: The dried blast furnace nickel slag, carbide slag, municipal waste incineration ash were ground and then sieved, and the sieved powdered blast furnace nickel slag, carbide slag, municipal waste incineration ash and dried fly ash microbeads were mixed to obtain a composite powder; S3. Raw material ratio: Weigh the solid sodium carbonate particles in parts by weight; S4. Mixing and stirring: Add nano silicon dioxide and nano titanium dioxide to part of the water and dissolve them completely by physical methods; then pour the composite powder in S2 and the solid sodium carbonate particles in the proportion in S3 into a mixer and dry mix at a low speed; then pour the remaining water, tartaric acid, sodium citrate and the suspension of nano silicon dioxide and nano titanium dioxide into the mixer, mix them thoroughly to obtain the prepared nano-modified alkali-activated multi-component composite cementitious material; finally, add coal gangue and gold tailings as coarse and fine aggregates, stir them thoroughly to obtain nano-modified alkali-activated concrete, i.e., nano-modified all-solid waste mine filling material.
3. The method for preparing the nano-modified all-solid waste mine filling material according to claim 2, characterized in that: The drying time in S1 is more than 12 hours, and the drying temperature is controlled at 45-60°C.
4. The method for preparing the nano-modified all-solid waste mine filling material according to claim 2, characterized in that: The grinding time in S2 is 50 min-70 min, and the sieving in S2 is to pass through a 200-mesh sieve.
5. The method for preparing the nano-modified all-solid waste mine filling material according to claim 2, characterized in that: The dry mixing time in S4 is 30 s-50 s; after the remaining water, tartaric acid, sodium citrate and nano-silicon dioxide and nano-titanium dioxide suspension in S4 are poured into the mixer and rotated and stirred for 50 s-60 s, coarse and fine aggregates are added to S4 and rotated and stirred for 100 s-120 s.
6. The method for preparing the nano-modified all-solid waste mine filling material according to claim 2, characterized in that: The physical method in S4 includes one or both of mechanical stirring and ultrasonic dispersion.
7. The method for preparing the nano-modified all-solid waste mine filling material according to any one of claims 3 to 6, characterized in that: The sodium carbonate is 4 parts; the water is 35 parts; the CaO content in the carbide slag is 96%; the SiO2 content in the fly ash microspheres is 59.4%, the Al2O3 content is 23.3%, and the Fe2O3 content is 5.5%; the SiO2 content in the blast furnace nickel slag is 33.15%, the CaO content is 22.5%, and the Al2O3 content is 21.94%; the SiO2 content in the municipal waste incineration ash is 31.2%, and the CaO content is 53.9%; the drying time in S1 is 24 h; the grinding time in S2 is 70 min; the grinding time in S2 is 70 min; the physical method in S4 includes mechanical stirring and ultrasonic dispersion.
8. A building material, characterized in that: It includes the nano-modified all-solid waste mine filling material described in claim 1 or the nano-modified all-solid waste mine filling material prepared by any preparation method of claims 3-6.
9. Use of the nano-modified all-solid waste mine filling material according to claim 1 or the nano-modified all-solid waste mine filling material prepared by any preparation method of claims 2-6 in mine backfilling projects, construction projects, bridge projects, highway projects or tunnel projects.
Citation Information
Patent Citations
Solid waste based coastal karst green filling material and preparation method and application thereof
CN112358270A
Method for preparing cemented filling material through cooperation of multi-source industrial waste residues and superfine tailings
CN116639945A